2015
DOI: 10.1007/s00296-015-3316-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome in a cohort of systemic lupus erythematosus patients from Northeastern Brazil: association with disease activity, nephritis, smoking, and age

Abstract: Systemic lupus erythematosus (SLE), an autoimmune inflammatory disease, is associated with an increased prevalence of accelerated atherosclerosis and cardiovascular events. Metabolic syndrome (MetS) is a set of cardiovascular risk factors in SLE patients, which may lead to a proinflammatory condition and increased morbidity and mortality. The objective of this study was to evaluate the prevalence of MetS in a cohort of SLE patients versus healthy controls, and to analyze the association of clinical and demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 40 publications
1
24
2
2
Order By: Relevance
“…We found a statistically higher number of smokers among DLE patients than among controls and the number of cigarettes smoked daily was higher in patients with DLE, as found in other case-control reports. In previous studies, it has been determined by Negrón et al that smoking status in SLE patients with MetS did not show any significance when compared to the control group while Mederios et al reported that SLE patients with MetS were higher smokers when compared to the patients without MetS [12, 13]. In our study, no significance was observed in terms of smoking habits between the DLE patients with and without MetS.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…We found a statistically higher number of smokers among DLE patients than among controls and the number of cigarettes smoked daily was higher in patients with DLE, as found in other case-control reports. In previous studies, it has been determined by Negrón et al that smoking status in SLE patients with MetS did not show any significance when compared to the control group while Mederios et al reported that SLE patients with MetS were higher smokers when compared to the patients without MetS [12, 13]. In our study, no significance was observed in terms of smoking habits between the DLE patients with and without MetS.…”
Section: Discussioncontrasting
confidence: 64%
“…Unsurprisingly, it was an expected result to find lower ratio of arterial HT in DLE patients with MetS when compared to the SLE patients with MetS. In the previous studies, older age in SLE patients has been notified with MetS similar to our DLE patients; however, different from our study, as can be interpreted as higher inflammation burden in SLE, higher BMI, longer disease duration, and higher disease activity have been found in SLE patients with MetS when compared to the patients without MetS [13, 14]. …”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Com base em fatores relacionados aos mecanismos inflamatórios no lúpus eritematoso sistêmico e ao uso prolongado de glicocorticoides, infere-se que a prevalência de SM parece ser aumentada na população com lúpus eritematoso sistêmico que na população geral. Entretanto os achados são controversos, por um lado trabalhos anteriores descrevem maior prevalência de SM em lúpus eritematoso sistêmico, outros por sua vez apontaram achados sem significância estatística quando comparados com grupo controle saudável (Medeiros et al, 2016).…”
Section: Síndrome Metabólica E Doenças Autoimunes Sistêmicasunclassified